Important Issues to Severe Trauma Survivors: A Qualitative Study. Issue 1 (January 2022) - James, Arthur; Tran, Viet-Thi; Gauss, Tobias; Hamada, Sophie; Roquet, Florian; Bitot, Valérie; Boutonnet, Mathieu; Raux, Mathieu; Ravaud, Philippe
Abstract : Objective: Identify issues that are important to severe trauma survivors up to 3 years after the trauma. Background: Severe trauma is the first cause of disability-adjusted life years worldwide, yet most attention has focused on acute care and the impact on long-term health is poorly evaluated. Method: We conducted a large-scale qualitative study based on semi-structured phone interviews. Qualitative research methods involve the systematic collection, organization, and interpretation of conversations or textual data with patients to explore the meaning of a phenomenon experienced by individuals themselves. We randomly selected severe trauma survivors (abbreviated injury score ≥3 in at least 1 body region) who were receiving care in 6 urban academic level-I trauma centers in France between March 2015 and March 2018. We conducted double independent thematic analysis. Issues reported by patients were grouped into overarching domains by a panel of 5 experts in trauma care. Point of data saturation was estimated with a mathematical model. Results: We included 340 participants from 3 months to 3 years after the trauma [median age: 41 years (Q1–Q3 24–54), median injury severity score: 17 (Q1–Q3 11–22)]. We identified 97 common issues that we grouped into 5 overarching domains: body and neurological issues (29 issues elicited by 277 participants), biographical disruption (23 issues, 210 participants), psychological and personality issues (21 issues, 147 participants), burden of treatment (14 issues, 145 participants), and altered relationships (10 issues, 87 participants). Time elapsed because the trauma, injury location, or in-hospital trauma severity did not affect the distribution of these domains across participants' answers. Conclusions: This qualitative study explored trauma survivors' experiences of the long-term effect of their injury and allowed for identifying a set of issues that they consider important, including dimensions that seem overlooked in trauma research. Our findings confirm that trauma is a chronic medical condition that demands new approaches to post-discharge and long-term care. Abstract : Supplemental Digital Content is available in the text